2020
DOI: 10.1016/j.jhep.2020.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Alternatively activated macrophages promote resolution of necrosis following acute liver injury

Abstract: BMDMs Phagocytosis Necrotic hepatocytes Proinflammatory cytokines Crosstalk with innate immune system AAMs Infiltrating neutrophils +IL-4 +IL-13 Endothelial cell proliferation Growth factors Central vein Highlights Primary BMDMs localised to liver and spleen within hours following intravenous injection in mice. AAMs were highly phagocytic and i.v. transfer elicited reductions in necrotic area, HMGB1 translocation, and hepatic neutrophil infiltration. AAM injection reduced inflammatory mediators and stimulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(117 citation statements)
references
References 42 publications
5
111
0
1
Order By: Relevance
“…49,76,141 Expression of these genes enables wound healing, clearance of dead cells, and promotion of hepatocyte proliferation, thereby allowing the liver to return to homeostasis after injury and fibrosis. 49,139,142,143 In mice challenged by APAP overdose, preventing monocyte infiltration by neutralization of CCR2 results in the absence of Ly6C low MoMϕs and thus a lack of tissue inflammation resolution and the accumulation of late apoptotic neutrophils. 143 Conversely, injection of BM-derived alternative activated macrophages, which are primarily Ly6C low MoMϕs, stimulates hepatocyte proliferation and accelerates recovery of the liver from APAP-induced necrosis.…”
Section: Roles Of Macrophages In Resolving Inflammation During Liver mentioning
confidence: 99%
See 1 more Smart Citation
“…49,76,141 Expression of these genes enables wound healing, clearance of dead cells, and promotion of hepatocyte proliferation, thereby allowing the liver to return to homeostasis after injury and fibrosis. 49,139,142,143 In mice challenged by APAP overdose, preventing monocyte infiltration by neutralization of CCR2 results in the absence of Ly6C low MoMϕs and thus a lack of tissue inflammation resolution and the accumulation of late apoptotic neutrophils. 143 Conversely, injection of BM-derived alternative activated macrophages, which are primarily Ly6C low MoMϕs, stimulates hepatocyte proliferation and accelerates recovery of the liver from APAP-induced necrosis.…”
Section: Roles Of Macrophages In Resolving Inflammation During Liver mentioning
confidence: 99%
“…143 Conversely, injection of BM-derived alternative activated macrophages, which are primarily Ly6C low MoMϕs, stimulates hepatocyte proliferation and accelerates recovery of the liver from APAP-induced necrosis. 142 Phagocytosis of dead cells (efferocytosis) is a major mechanism that promotes the switch of Ly6C high MoMϕs to Ly6C low MoMϕs (Fig. 1).…”
Section: Roles Of Macrophages In Resolving Inflammation During Liver mentioning
confidence: 99%
“…In an experimental model of acute liver injury, adoptive transfer of ex vivo IL-4/IL-13-polarized BMDM rapidly reduced liver injury and several mediators of inflammation. 163 Of note, the adoptive transfer of primary humanpolarized monocyte-derived MФ partially recapitulated the therapeutic effect observed with polarized mouse BMDM in the same mouse model. 163 Similarly, injection of BMDM or embryonic stem cell-derived MФ reduced both fibrosis and improved liver regeneration in a hepatic injury and fibrosis model.…”
Section: Adoptive Transfermentioning
confidence: 84%
“…This reveals possible communication signals between macrophage subpopulations. 28 In addition, elucidation of neutrophil-macrophage interactions has shown that ROS secreted by neutrophils orchestrate the switch to proresolving macrophages. This shows that ROS, primarily known for their role in the initiation of inflammation, also have resolution-inducing effects.…”
Section: Macrophagesmentioning
confidence: 99%
“…The therapeutic efficacy was partially replicated with the use of human-derived alternatively activated macrophages in mice and its potential as a novel therapy is intriguing. 28 Interestingly, a recent study has shown the efficacy of administrating classically activated macrophages ("M1") in the amelioration of CCl4 or BDLinduced liver fibrosis. They exhibited stronger therapeutic effects when compared with the administration of nonpolarized ("M0") or alternative activated macrophages ("M2").…”
Section: Therapeutic Implicationsmentioning
confidence: 99%